Cumulative effects of concussion history on baseline computerized neurocognitive test scores: Systematic review and meta-analysis - Alsalaheen, B.; Stockdale, K.; Pechumer, D.; Giessing, A.; He, X.; Brogli, S. P. (Sports Health: A Multidisciplinary Approach, 2017)
It is unclear whether individuals with a history of single or multiple clinically recovered concussions exhibit worse cognitive performance on baseline testing compared with individuals with no concussion history. Objective: To analyze the effects of concussion history on baseline neurocognitive performance using a computerized neurocognitive test. Data sources: PubMed, CINAHL, and psycINFO were searched in November 2015. The search was supplemented by a hand search of references. Study Selection: Studies were included if participants completed the Immediate Post-concussion Assessment and Cognitive Test (ImPACT) at baseline (ie, preseason) and if performance was stratified by previous history of single or multiple concussions. Study Design: Systematic review and meta-analysis. Level of Evidence: Level 2. Data Extraction: Sample size, demographic characteristics of participants, as well as performance of participants on verbal memory, visual memory, visual-motor processing speed, and reaction time were extracted from each study. Results: A random-effects pooled meta-analysis revealed that, with the exception of worsened visual memory for those with 1 previous concussion (Hedges g = 0.10), no differences were observed between participants with 1 or multiple concussions compared with participants without previous concussions. Conclusion: With the exception of decreased visual memory based on history of 1 concussion, history of 1 or multiple concussions was not associated with worse baseline cognitive performance